The Relationship Between Optimism And Student engagement In Sman X Padang Students - Nabilah, Farah Salsabil; Maputra, Yantri; Nasa, Amatul Firdausa; Susanti, Meria; Afriyeni, Nelia (Mediapsi, 2025)
Student behavior problems such as truancy, neglect of assignments, and lack of activity in the learning process indicate low student involvement. One thing that can play an important role in increasing student engagement is creating optimism among students. This research aims to determine the relationship between optimism and student engagement among students at SMAN X Padang City. The research method used in this research is a quantitative method using the Pearson Product Moment analysis method. The respondents in this study were 281 students of SMAN X Padang City who were obtained using the proportionate stratified random sampling technique. Data collection was carried out using an adaptation of the "School Engagement" and "Life Orientation Test-Revised" (LOT-R) measuring tools. The results of this study show that there is a significant positive relationship between optimism and student engagement (p = <.05; r = .257). This shows that, the higher the optimism among students, the higher the student engagement among SMAN X students in Padang City and vice versa.